MUTU TAPAI BERAS KETAN PUTIH DENGAN PENAMBAHAN BUAH NAGA SEBAGAI PEWARNA ALAMI - Hana Nita Isnaini; Adi Saputrayadi; Desy Ambar Sari (The Journal of Teknologi Pangan, 2022)
Tapai is a traditional food that is still widely found in traditional markets made through the fermentation process using the help of yeast. The purpose of this study was to find out the effect of the addition of red dragon fruit extract on the quality of white glutinous rice tapai that panelists liked. The method used in this study is an Experimental method arranged with a Complete Random Design (RAL) with the treatment of adding red dragon fruit extract to the manufacture of white glutinous rice tapai consisting of 5 (five) treatments, namely: P1 (15% red dragon fruit extract), P2 (20% red dragon fruit extract), P3 (25% red dragon fruit extract), P4 (30% red dragon fruit extract) and P5 (35% red dragon fruit extract). Significant parameters are further tested using the Honest Real Difference (BNJ) advanced test at a real level of 5%. The results showed that the addition of red dragon fruit extract had a real effect on the chemical properties of alkohol content parameters, reduced sugar content, divorce level (L) and organoleptic properties of texture, taste and color value scores, but had no real effect on the pH levels and aroma scores of white glutinous rice tapai observed. The best treatment in making white glutinous rice tapai with the addition of red dragon fruit extract is obtained in the P4 treatment (addition of 30% red dragon fruit extract) which has an alcohol content of 8.79%, reduced sugar content of 24.73%, pH content of 3.57 and brightness level (L) 47.16 with a taste of likes, very red color, a slightly scented tapai aroma and a slightly mushy texture.